Thermodynamics of Biosorption for Removal of Co(II) Ions by an Efficient and Ecofriendly Biosorbent (Saccharum bengalense): Kinetics and Isotherm Modeling. (2nd October 2012) - Imran Din, Muhammad; Mirza, Muhammad Latif; Ata, Sadia; Athar, Makshoof; Mohsin, Ijaz Ul
Abstract : In this research work, a low-cost biomass derived from the pulp of Saccharum bengalense (SB) was used as an adsorbent material/biosorbent for the removal of Co(II) ions from aqueous solution. Langmuir, Freundlich Timken, and Dubinin-Radushkevich (D-R) adsorption isotherms have been applied to further define the mechanism of sorption. From the comparison of different adsorption isotherm models, it was found that biosorption of Co(II) by SB followed Langmuir and Freundlich models. The sorption capacity for cobalt of Saccharum bengalense was (q m = 14.7  mg/g) at 323K. A comparison of kinetic models applied to the adsorption of Co(II) onto Saccharum bengalense was evaluated for the pseudo-first-order, pseudo-second-order, Elovich, and intraparticle diffusion and Bangham's kinetics models. It was found that the pseudo-second-order mechanism is predominant. Activation parameters evaluated from thermodynamics and kinetic parameters such as free energy change ( Δ G 0 = −0.254, Δ G # = 84.63  kJ/mol), enthalpy change ( Δ H 0 = + 22.24, Δ H # = 0.004  kJ/mol), and entropy change ( Δ S 0 = 0.065, Δ S # = 0.262  kJ/mol) revealed the spontaneous, endothermic, and feasible nature of adsorption process. The results of the present investigation suggested that Saccharum bengalense (SB) can be used as an environmentally and economically feasible biosorbent for the removal of Co(II) from aqueous solutions.